Mixed-genotypes infections with hepatitis C virus in hemodialysis subjects. - Hamzah, Hairul Aini; Mustafa Mahmoud, Mohammed Imad Al-Deen; MR, Seman; BA, Nasuruddin (Malaysian Medical Association, 2012)
Mixed-genotypes hepatitis C virus (HCV) infections are normally ignored in chronic hemodialysis patients. The aim of this study is to investigate the prevalence of mixed-genotypes infections among hemodialysis patients in Pahang province, Malaysia. Reverse-transcription and polymerase chain reaction methods were performed using two different sets of primers, targeting the 5' untranslated region and nonstructural 5B region. Target region base sequences were obtained by direct sequencing. Discrepancy in outcomes from phylogenetic analysis of both regions suggests double infections. Of 40 subjects in eight hemodialysis centres, evidence of mixed-genotypes infections was found in 5 subjects (12.5%) from three different centres. Four patients were infected with mixed genotypes 3 and 1 and one with genotypes 3 and 4. Cases of mixed HCV genotypes infection were considered high among hemodialysis patients in Pahang. However, further investigation is needed to confirm whether they are true mixed infections or perhaps infection with recombinant virus and also to assess the clinicopathologic characteristics of the infection.